"STUDY OF CLINICAL PROFILE OF CASES WITH LIVER ABSCESS AND ITS CORRELATION WITH GLYCEMIC STATUS’’ - Dr. Pranjal Peepre; Prof. Dr. Ajay Pal Singh (M.D.) (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Liver is an important vital organ of the body. This organ is subjected to numerous systemic infections viral, bacterial and parasitic and lies at the distal end of the portal circulation; it is therefore bathed with portal blood containing viruses, bacteria, parasites, ova, products of digestion and other antigens. Hepatic or liver abscesses are infectious, space-occupying lesions in the liver; the two most common abscesses being pyogenic and amoebic. Pyogenic liver abscess (PLA) is a rare but potentially lethal condition, with a reported incidence of 20 per 100000 hospital admissions in a western population. Its severity depends on the source of the infection and the underlying condition of the patient. Amoebic liver abscesses (ALA) are common in tropical regions mainly where ‘Entamoeba histolytica’ is endemic and is more prevalent in individuals (mostly young males) with suppressed cell mediated immunity. In both the types of hepatic abscesses, right lobe of the liver is the most likely site of infection. The clinical presentation of both the types may be elusive with combination of fever, right upper quadrant pain and hepatomegaly with or without jaundice.1